Paternalistic Leadership and Safety Participation of High-Speed Railway Drivers in China: The Mediating Role of Leader–Member Exchange - Zhang, Na; Liu, Shuzhen; Pan, Bowen; Guo, Ming (Frontiers in Psychology, 2021)
This research aimed to examine the effects of paternalistic leadership on the safety participation of high-speed railway drivers. Survey data were collected from 601 drivers in major Chinese rail companies. Structural equation modeling was conducted to analyze the influence of paternalistic leadership on safety participation via leader-member exchange (LMX). The results indicated that moral leadership directly promotes safety participation. Besides, benevolent leadership was positively associated with safety participation. Also, LMX partially mediates the positive relationship between benevolent leadership, moral leadership and safety participation. Therefore, paternalistic leadership promotes the safety participation of high-speed railway drivers.